TRANSPLANTATION OF AUTOLOGOUS MESENCHYMAL STEM CELLS IN THE EXPERIMENTAL MYCOBACTERIAL INFECTION: IMPACT OF CONDITIONING - Ya. Sh. Shvarts; S. N. Belogorodtsev; P. N. Filimonov; A. G. Cherednichenko (Туберкулез и болезни лёгких)
The use of mesenchymal stem cells (MSC) in immune therapy of drug resistant tuberculosis is to be experimentally justified. The impact of non-conditioned and poly(A:U)-conditioned MSC on the course of BCG-infection in mice has been studied. It has been proved that double administration of MSC to mice of BALB/c line in 11 and 12.5 weeks after infection with BCG caused significant reduction of granulomas formation and activated the mycobacterial growth. On the contrary the similar administration of MSC with poly(A:U) conditioning significantly inhibited the mycobacterial growth and provided no effect on granulomas formation. Non-conditioned MSC manifested immune suppression properties, and poly(A:U) conditioning caused their pro-inflammatory polarization in vitro. It has been concluded that MSC therapy of mycobacterial infection can be effective in case of targeted formation of pro-inflammatory immune-phenotype of MSC.